2021
DOI: 10.3390/app11041550
|View full text |Cite
|
Sign up to set email alerts
|

Using Recognizable Fuzzy Analysis for Non-Destructive Detection of Residual Stress in White Light Elements

Abstract: The phenomenon of residual stress in optical lens injection molding affects the quality of optical devices, with the refractive errors that are caused by geometric errors being the most serious, followed by the reduced accuracy and function of optical components; it is very important to ensure that the lens geometry remains intact and that the refractive index is reduced. This paper uses a photoelastic stress compensation method for measurement verification along with fuzzy theory to reorganize a set of proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Han-Jui Chang [ 11 ] used an identifiable method of photoelastic stress for measurement and compensation, combined with fuzzy theory, to reorganize a process that can be used to evaluate product re-residual stresses, resulting in an effective quantification and compensation measurement of residual stresses in products with the corresponding theoretical formulation. In 2015, Macías et al [ 12 ] found that the quality of optical components made of transparent thermoplastic polymers depends on the presence of residual stresses, and that the wrong choice of process parameters can lead to the generation of residual stresses in plastic lenses, while residual stresses in the components can significantly affect the structural dimensions of the lenses and their dimensional accuracy.…”
Section: Literature and Reviewmentioning
confidence: 99%
“…Han-Jui Chang [ 11 ] used an identifiable method of photoelastic stress for measurement and compensation, combined with fuzzy theory, to reorganize a process that can be used to evaluate product re-residual stresses, resulting in an effective quantification and compensation measurement of residual stresses in products with the corresponding theoretical formulation. In 2015, Macías et al [ 12 ] found that the quality of optical components made of transparent thermoplastic polymers depends on the presence of residual stresses, and that the wrong choice of process parameters can lead to the generation of residual stresses in plastic lenses, while residual stresses in the components can significantly affect the structural dimensions of the lenses and their dimensional accuracy.…”
Section: Literature and Reviewmentioning
confidence: 99%
“…In addition, there are blind spots in the physical experiment formula. In 2021, Han-Jui Chang [ 19 ] used the identifiable method of photoelastic stress for measurement and compensation combined with fuzzy theory to reorganize a set of processes that can be used to evaluate product residual stress. The corresponding theoretical formula can be used to effectively quantify and compensate for the measurement of the residual stress of the product.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The higher the mold temperature, the lower the maximum residual stress. In 2021, Hanjui Chang et al [ 5 ] proposed a method to evaluate the residual stress of products based on fuzzy theory and used the photoelastic stress compensation method for measurement verification. This method can effectively quantify and measure the residual stress of products and provide an identifiable and reliable correction basis for subsequent mold maintenance or parameter adjustment.…”
Section: Introductionmentioning
confidence: 99%